Effect of insecticides on boll weevil populations and beneficial arthropods on cotton fields using trap crop residues - Soares, José Janduí; Yamamoto, Pedro Takao; Gravena, Santin; Busoli, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 1994)
This research was conducted in Jaboticabal, SP, Brazil, during the season of 1990/91. The purpose was to study the efficiency of insecticide for boll weevil (Anthonomus grandis Boheman) control by using a trap crop residue. The statistical design followed the randomized blocks with four treatments and four replications. The treatments were: 1) endosulfan 0,7 kg AI/ha; 2) deltamethrin 0.015 kg AI/ha; 3) methyl parathion 0.6 kg AI/ha; 4) check (no insecticide). The evaluations were made before and at 1 and 7 days after the sprayings. The results showed that: a) deltamethrin was efficient for boll weevil control; b) endosulfan showed to be selective to arthropod predators associated to trap crop residues left after the harvest for boll weevil attraction and control; c) endosulfan and parathion were medianly efficient; d) parathion and deltamethrin showed to be little selective.